Phonic Methods on Increasing Reading Ability in Children with Visual Impairments - Nursina, Aulia (JASSI ANAKKU, 2021)
Reading is an ability that must be possessed by every child, including children with special needs. This is the background of this study which aims to determine the extent of the influence of the phonic method on improving early reading skills in children with visual impairments. The research method used is an experimental method with a Single Subject Research (SSR) approach using an Applied Behavior Analysis (A-B-A) design. The presentation of the data is processed and analyzed using descriptive statistics with percentages and is displayed in graphical form. The results showed that the mean acquisition for each condition, namely the baseline phase 1 (Applied-1) was 52.50%, the intervention phase (Behavior) was 65.35%, and the baseline phase 2 (Analysis-2) increased to 87.50%. Based on the results of the study, it was shown that the phonic method affected increasing the ability to read early in children with visual impairments. Therefore, this study can provide an alternative learning strategy for teachers in improving early reading skills in children with visual impairments using the phonic method.